Oral and radiological features of mucormycosis in post-Covid patients – a clinical study - Nitish Kumar Kompalli; Rohit Kumar Kompalli; Soumya Athota (Romanian Journal of Infectious Diseases)
Introduction. Mucormycosis, commonly referred to as “black fungus,” has emerged as a life-threatening opportunistic infection, particularly in post-COVID patients. This study aims to evaluate the clinical, radiological, and treatment-related features of mucormycosis in post-COVID patients and assess their outcomes. Materials and methods. This observational clinical study was conducted from April 2021 to October 2021, involving 50 consecutive post-COVID patients who presented with clinical and radiological features of mucormycosis. Demographic data, clinical symptoms, comorbidities, laboratory investigations, radiological findings, and treatment details were collected. Patients underwent computed tomography (CT) to assess bone involvement, sinus, and orbital involvement. Treatment regimens, including antifungal therapy and surgical interventions, were recorded. Patients were followed up for recurrence and long-term outcomes. Results. The majority of the patients were males (58%) and in the 31-45 age group (34%). Diabetes mellitus (60%) and steroid use (80%) were the most common comorbidities. Clinically, 70% of patients presented with soft tissue swelling or necrosis, and 44% had black eschar on the palate. CT findings revealed maxillary bone involvement in 56% of cases and sinus involvement in 50%. Orbital involvement was noted in 20%. Amphotericin B was the most commonly used antifungal therapy (70%), and 60% of patients underwent debridement. The overall recovery rate was 70%, with a recurrence rate of 16%. Facial deformities or ongoing oral issues were noted in 24% of patients during follow-up. Conclusion. Mucormycosis in post-COVID patients is associated with high morbidity, particularly in those with diabetes and those treated with corticosteroids. Antifungal therapy combined with surgical intervention yielded a 70% recovery rate, although recurrence and long-term complications were observed. Early diagnosis, appropriate antifungal therapy, and aggressive surgical management are critical to improving outcomes. Preventive strategies, including better management of comorbidities and judicious use of steroids, are essential in reducing the burden of mucormycosis in post-COVID patients.